An Empirical Analysis of the Pricing of Mortgage-Backed Securities: Discussion - Thurbull, S. M. (Journal of Finance, 1983)
S. M. Thurbull, An Empirical Analysis of the Pricing of Mortgage-Backed Securities: Discussion, The Journal of Finance, Vol. 38, No. 2, Papers and Proceedings Forty-First Annual Meeting American Finance Association New York, N.Y. December 28-30, 1982 (May, 1983), pp. 646-647